Anonymous hierarchical identity-based encryption with bounded leakage resilience and its application. (2017) - Hu, Chengyu; Liu, Pengtao; Guo, Shanqing; Xu, Qiuliang
Hierarchical identity-based encryption can be used to protect the sensitive data in cloud system. However, as the traditional security model does not capture side-channel attacks, many hierarchical identity-based encryption schemes do not resist this kind of attack, which can exploit various forms of unintended information leakage. Inspired by these, leakage-resilience cryptography formalises some models of side-channel attacks. In this paper, we consider the memory leakage resilience in anonymous hierarchical identity-based encryption schemes. By applying Lewko et al.'s tools, we construct a master key leakage-resilient anonymous hierarchical identity-based encryption scheme based on dual system encryption techniques. As an interesting application of our scheme, we consider security for public-key encryption with multi-keyword ranked search (PEMKRS) in the presence of secret key leakage in the trapdoor generation algorithm, and provide a generic construction of leakage-resilient secure PEMKRS from a master key leakage-resilient anonymous hierarchical identity-based encryption scheme.